2013
DOI: 10.1123/jpah.10.6.900
|View full text |Cite
|
Sign up to set email alerts
|

How Can Mass Participation Physical Activity Events Engage Low-Active People? A Qualitative Study

Abstract: Mass participation events have potential to engage low-active people. The impact of participation resonated with factors that are positively associated with physical activity in other settings, and event characteristics matched key criteria for attracting low-active groups identified through social marketing research. Suggestions are given for how to capitalize on the findings for health promotion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The motivational factors identified in the literature that enhance sport event participation (e.g., socialization, performance, and excitement) might fulfill these basic needs and be sources for autonomous motivation (Funk, 2008). Early and Corcoran (2013) studied the experience of 14 non-active people participating in running and walking events in Cambridge and confirmed that the events in their study had the potential to engage non-active people in exercise who experienced a sense of achievement, atmosphere, and relatedness. However, the event had a short-term perspective, namely, training and succeeding in completing the distance at the event, while maintaining exercise behavior has a more long-term perspective.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…The motivational factors identified in the literature that enhance sport event participation (e.g., socialization, performance, and excitement) might fulfill these basic needs and be sources for autonomous motivation (Funk, 2008). Early and Corcoran (2013) studied the experience of 14 non-active people participating in running and walking events in Cambridge and confirmed that the events in their study had the potential to engage non-active people in exercise who experienced a sense of achievement, atmosphere, and relatedness. However, the event had a short-term perspective, namely, training and succeeding in completing the distance at the event, while maintaining exercise behavior has a more long-term perspective.…”
Section: Introductionmentioning
confidence: 86%
“…Based on the insights from the scarce literature on the relationships between motivation to participate and exercise behavior in the context of a mass sport event (Titze et al, 2005; Funk et al, 2011; Early and Corcoran, 2013), the following hypothesis is formulated.…”
Section: Introductionmentioning
confidence: 99%
“…The highest-rated factor in the threats category was maintaining participant enthusiasm (T5). To attract residents to continue to participate, it is necessary to maintain the enthusiasm of already participating residents 56 . The key to maintaining the participants’ enthusiasm is to increase their satisfaction and motivation.…”
Section: Discussionmentioning
confidence: 99%
“…Amateur sports match marketing components include introducing the event to the public, attracting residents to participate, and attracting media to cover the event. Attracting residents to participate continuously must ensure that the focus is on keeping the enthusiasm of those who have already participated and their second participation [44]. The key to maintaining the participants' enthusiasm is to meet their expectations of the participants and satisfy their needs.…”
Section: Discussionmentioning
confidence: 99%